Anatomy and Impact of Export Promotion Agencies - Cruz, Marcio (World Bank, Washington, DC, 2018)
Recent literature has shown evidence of positive contributions of export promotion agencies around the world in raising exports, through the intensive and extensive margins of trade. The number of export promotion agencies has increased substantially over the past two decades, and most of them focus on assisting exporters in understanding and finding markets for their products. This paper describes the characteristics of export promotion agencies around the world, using a novel database from the World Bank, in collaboration with the International Trade Center in Geneva, covering 2005-10. In addition, it presents a short summary of the literature on the impacts of export promotion agencies.